Pengaruh Switching Costs terhadap Customer Retention pada Industri Perbankan di Indonesia - Simbolon, Freddy (Binus Business Review, 2011)
The number of frequent troubles at one bank may cause a decrease of customer trust. Customer will reconsider whether continuing to safe their deposits or moving to other banks. One factor that may influence the customer retention is the switching costs, that are the fee which must be borne by the customer along the transformations of one product to a service or a service to a product or even a certain service to another service. In fact switching costs will not only appear just as a consequence when a transformation is done or appear only as an economic cost. But when one process of transformation happens, many possibilities of cost may arise such as procedural costs, financial loss costs and psychological loss costs. Therefore the correct determination about switching costs might be an important information for customers so that they may consider the relevant costs arise when they decide to move to other banks. If the costs they will have to bear exceeds the benefit they will get, it is expected that they will reconsider to stay faithful and diminish their desire to move to other banks.